Therapeutic targeting of microRNAs: current status and future challenges - Li, Zhonghan; Rana, Tariq M. (Nature reviews. Drug discovery, 2014)
Key Points MicroRNAs (miRNAs) have important roles in many aspects of human diseases, and their targeted inhibition may have substantial therapeutic impact. Inhibition of miRNAs can be achieved through a variety of methods and chemically modified antisense oligonucleotides (anti-miRs) have shown the most prominent effects. Targeted delivery of anti-miRs is crucial to achieve intended therapeutic effects, and further efforts are warranted to develop more efficient delivery systems. MicroRNAs (miRNAs) — 21- to 23-nucleotide single-stranded RNAs that regulate gene expression — have roles in numerous diseases, and are therefore attractive therapeutic targets. Li and Rana discuss strategies in the design of miRNA-targeting oligonucleotides with increased efficacy and improved in vivo delivery characteristics, and highlight some of the challenges that lie ahead in the clinical development of these therapeutics. MicroRNAs (miRNAs) are evolutionarily conserved small non-coding RNAs that have crucial roles in regulating gene expression. Increasing evidence supports a role for miRNAs in many human diseases, including cancer and autoimmune disorders. The function of miRNAs can be efficiently and specifically inhibited by chemically modified antisense oligonucleotides, supporting their potential as targets for the development of novel therapies for several diseases. In this Review we summarize our current knowledge of the design and performance of chemically modified miRNA-targeting antisense oligonucleotides, discuss various in vivo delivery strategies and analyse ongoing challenges to ensure the specificity and efficacy of therapeutic oligonucleotides in vivo . Finally, we review current progress on the clinical development of miRNA-targeting therapeutics.